Pengaruh Koneksi Politik dan Corporate Governance terhadap Kinerja Keuangan - Pratiwi, Dhona; Hariyati, Hariyati (Universitas Negeri Surabaya, 2024)
This research has purpose to determine the effect of political connections and corporate governance on financial performance. The population used are the mining sector companies which listed on the Indonesia Stock Exchange in 2016-2018 with a total sample of 39 companies based on purposive sampling technique. Political connections are measured using dummy variables, corporate governance used corporate governance mechanisms, and financial performance used Return on Assets (ROA). Data analysis techniques used multiple linear regression analysis helped by SPSS. The results show that political connections, audit committees, institutional ownership, and managerial ownership have no effect on the financial performance. Meanwhile, the independent board of commissioners has a negatif ieffect on financial iperformance.